Determinan Niat Keberlanjutan Penggunaan Pembayaran Digital QRIS Indonesia: Bukti Peran Mediasi Kepercayaan di Kota Tanjungpinang - Wibowo, Putera Ramadhan Susatria; Ambarita, Vonny Rianty; Dahlia, Diajeng Putri; Husna, Asmaul (Program Studi Manajemen FEBM UMRAH, 2026)
This study aims to analyze the determinants of Continuance Intention to Use QRIS Indonesia’s Digital Payment, incorporating Trust as a mediating variable. A quantitative explanatory research approach was applied. Respondents consisted of QRIS users in Tanjungpinang City who had conducted at least three QRIS transactions within the last three months. Data were collected through an online questionnaire using a five point Likert scale. A total of 100 valid responses were analyzed using SEM PLS with smartpls version 4.1.1.4. The results show that Perceived Usefulness and Perceived Ubiquity have significant effects on Continuance Intention. Perceived Autonomy has no direct effect on Continuance Intention, but it significantly affects Trust. Trust is confirmed as the strongest predictor of Continuance Intention. Furthermore, Trust mediates the relationships between Perceived Ubiquity and Perceived Autonomy with Continuance Intention, but does not mediate the relationship between Perceived Usefulness and Continuance Intention. These findings highlight that trust plays a critical role in ensuring the continued use of QRIS, which is shaped by perceived benefits, broad accessibility, and user autonomy in digital payments. The study recommends improving security measures and expanding QRIS adoption to strengthen user trust and sustainable usage.